THE ROLE OF PRODUCT QUALITY IN THE INFLUENCE OF PRICE PERCEPTION AND PROMOTION ON PURCHASE DECISIONS IN E-COMMERCE - CAHYONO, FANNY AGUS; MARGARETHA, YOLLA; WINARTO, JACINTA (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
Information technology is developing very rapidly, as is the internet which also has a major impact on all aspects of life. Likewise, changes in trade and business in the world also have an impact on Indonesia. The presence of e-commerce in Indonesia is growing so rapidly. E-commerce not only provides support for the changing consumption methods and lifestyles of society, but also presents the latest economic opportunities for all individuals. This study aims to test the role of product quality on the influence of price perception and promotion on the decision to buy in e-commerce. The research sample was 100 people who had become consumers of one of Shopee, Tokopedia, Lazada and Bukalapak. The sampling technique applied purposive sampling. The data analysis technique applied multiple regression tests and Moderated Regression Analysis (MRA) tests. The results of the study showed that Promotion and price perception had a positive and significant effect on purchasing decisions. Product quality is able to moderate the influence of promotion on purchasing decisions and Product quality is able to moderate the influence of promotion on purchasing decisions. Keywords: Promotion, price perception, product quality, purchasing decisions.